Metalloporphyrins – An Update - Schulz, Stephanie; Wong, Ronald J.; Vreman, Hendrik J.; Strevenson, David K. (Frontiers in Pharmacology, 2012)
Metalloporphyrins are structural analogues of heme and their potential use in the management of neonatal hyperbilirubinemia has been the subject of considerable research for more than three decades. The pharmacological basis for using this class of compounds to control bilirubin levels is the targeted blockade of bilirubin production through the competitive inhibition of heme oxygenase (HO), the rate-limiting enzyme in the heme degradative pathway. Ongoing research continues in the pursuit of identifying ideal metalloporphyrins, which are safe and effective, by defining therapeutic windows and targeted interventions for the treatment of neonatal hyperbilirubinemia.